Desperately Seeking a Japanese Yokozuna - Giorgio Brunello; Eiji Yamamura (Institute of Labor Economics (IZA), 2023)
Using data on wrestlers and tournaments since the early 1970s, we study promotion practices in Sumo, a Japanese traditional sport. We show that, especially since 2010, foreign-born wrestlers trying to attain the second highest rank in Sumo were treated less favorably than Japanese born wrestlers. Similar practices, however, do not apply to foreign-born wrestlers competing for the top rank, probably because of the much higher public scrutiny attracted by promotions to this rank. Together with the 2010 Reform that effectively restricted access to foreign-born wrestlers, existing promotion practices may favor the return of Japanese born players to the top rank of the game.
Keywords: J40; J71; 330; promotion; Sumo; sports; Japan